The Manchester perspective on using the Design Project to enhance the education of chemical engineering students. Issue 6 (25th March 2021) - Kiss, Anton A; Webb, Colin
Abstract: The Design Project is a major piece of work for any undergraduate in chemical engineering, and it enables students to demonstrate skills and knowledge gained elsewhere in the degree programme alongside their own abilities to create and innovate. As such, the main learning process is activity based and associated with the undertaking of an open‐ended, but time‐limited, project that poses significant challenges to most students. Particularly in the UK context, the importance of the Design Project is recognized via its inclusion as a separate and very significant element in the accreditation of all engineering degrees. During the past decade, developments in the Chemical Engineering Design Project at the University of Manchester have led to international recognition and prestigious awards. This perspective article aims to identify the best education practices associated with the Manchester experience and to share these for the potential benefit of programmes elsewhere. The paper includes specific details regarding the module specifications, learning outcomes, organization of the Design Project activities, individual and team‐based work, reporting requirements, assessment procedures, and other aspects. The feedback received annually from students and fellow Design Project programme directors from other universities is also considered and the different perspectives are evaluated. © 2021 Society of Chemical Industry (SCI).